Counseling on Pulmonary TB Overcoming and Healthy House Sanitation for Pulmonary TB Patients - Nailul Hikmi; Naldi Candra; Mirza Aulia; Vitratul Illahi (Sustainable Applied Modification Evidence Community (SAMEC), 2024)
Tuberculosis (TB) is an infectious disease caused by Mycobacterium tuberculosis and spreads through the air when sufferers cough, sneeze or spit. TB is still a global health problem with 10 million cases in 2019 and 1.4 million deaths. Indonesia has a high TB incidence rate, with 316 per 100,000 population in 2018. Environmental factors such as ventilation, floor type and residential density greatly influence TB transmission. This research was conducted Community Health Center to measure the knowledge and sanitary conditions of TB patients' homes.  The methods used include interviews, counseling and direct observation of house conditions. The results show an increase in knowledge about TB after the education, with 75% of houses not meeting ventilation requirements, 8.9% of houses not meeting floor type requirements, 7.1% of houses not meeting wall type requirements, and 39.3% of houses having low occupancy density. not eligible. Good knowledge of a healthy environment and behavior that supports TB prevention is very important to reduce the transmission of this disease.